Recent decrease in DOC concentrations in Arctic lakes of southwest Greenland. Issue 16 (24th August 2015) - Saros, Jasmine E.; Osburn, Christopher L.; Northington, Robert M.; Birkel, Sean D.; Auger, Jeffrey D.; Stedmon, Colin A.; Anderson, Nicholas John
Abstract: A key indicator of changes in the terrestrial carbon cycle is shifting dissolved organic carbon (DOC) concentrations in surface waters. Arctic permafrost holds twice as much C as the atmosphere, thus recent warming and changes in atmospheric deposition to the region raise the need for a better understanding of how DOC is changing in arctic surface waters. In Kangerlussuaq, Greenland, lakewater DOC concentrations declined by 14 to 55% (absolute changes of 1 to 24 mg L −1 ) between 2003 and 2013, without significant changes in quality. Lakewater sulfate concentrations, but not chloride or conductivity, increased. These results suggest that similar to processes that have occurred at northern midlatitudes, increases in soil ionic strength as a result of sulfate enrichment may be linked to declining surface water DOC concentrations. Such enrichment may be occurring with enhanced non‐sea‐salt sulfate deposition. Our results reveal that rapid changes are occurring in the carbon cycle of this region of southwest Greenland. Key Points: Lakewater DOC in SW Greenland declined by 14 to 55% between 2003 and 2013 Lakewater sulfate concentrations, but not chloride or conductivity, increased Rapid change is occurring in the C cycle of this region